Evaluation of rheological properties and quality of xylitol-substituted dadih - Mohd Thani, Nurfatimah (2015)
Dadih is a dairy based dessert made of milk, water, sugar, and agar that is popular especially among South East Asian people. It has sweet taste due to high sugar content in its formulation. An excessive sugar intake is harmful to human health, and it would be beneficial if conventional sugar is replaced by a sugar substitute. In order to produce a healthier dadih, xylitol that has less energy and possesses sweetening power comparable to sucrose, was used as sugar substitute. To produce a new product such as xylitol substituted dadih, it is crucial to evaluate the suitable range of process parameters with various xylitol compositions in properties and quality. In this study, the evaluated properties were in terms of mechanical (rheological and texture) and thermal properties. Safety (total plate count and water activity) and sensory analysis were measured to evaluate the dadih quality. Thus, the first section of this current research was to investigate the effects of process conditions and xylitol concentrations in term of rheological and textural properties of dadih. Process conditions set up were cooking temperatures (85-95˚C) and cooking times (10-20 minutes) while the xylitol set up were at three levels of compositions (0%, 50%, and 100%). It was found that cooking temperature had the biggest impact on rheological and textural properties of dadih. All dadih samples showed an elastic characteristic (n’<1) with gel-like behavior where value of G’ (storage modulus) was higher than G” (loss modulus). In general, the presence of xylitol in dadih contributed to softer texture compared to product that is made from sucrose. Thus, xylitol substituted dadih prepared at 85C with cooking time 15 and 20 minutes have met the required texture in term of hardness and internal gel strength as the conventional dadih. The second section of this study focused on thermal and safety analysis of dadih prepared at temperature 85˚C with two points of cooking time (15 and 20 minutes). At both cooking time (15 or 20 minutes) as xylitol substitution increase, the onset temperature and enthalpy values were decreased, indicating a weaker structure of dadih with xylitol compared to sucrose. Dadih that was prepared with total xylitol (100%) exhibited the lowest onset temperature To (97.71±0.4˚C for 15 minutes and 99.85±0.18˚C for 20 minutes) and enthalpy values (2096.98±1.4 Jg-1 for 15 minutes and 2422.61±3.6 Jg-1 for 20 minutes). Dadih samples that demonstrated low values of onset temperature and melting enthalpy indicated that less energy was required to change the structure.Safety analysis was done to predict the stability and product quality of xylitol substituted dadih by evaluating microbial growth throughout the storage period of 25 days. From total plate count (TPC) and water activity analysis, all samples was totally spoiled at Day 25 where it contained >300 organism per gram and achieved maximum water activity value, aw (1). Spoilage of dadih with 100% xylitol was slightly prolonged, which was completely spoiled at Day 24 and 25, for 15 and 20 minutes cooking time respectively. However, dadih samples with total sucrose (0%) were observed to be spoiled earlier compared to the former, which was on Day 23. Extended shelf life and stability of dadih substituted xylitol might be due to natural characteristics of xylitol of having low water activity. Last section of this research was to evaluate the sensory analysis of the dadih. Based on eight attributes of sensory analysis, dadih that was prepared at 15 minutes cooking time for both total sucrose (0%) and xylitol (100%) was more preferable compared to samples 20 minutes cooking time. However, there were no significant differences (p > 0.05) for overall acceptability of both samples with 0% and 100% xylitol prepared at 15 minutes cooking time. Based on sensory evaluation, the score for dadih with xylitol substitute was above ‘slight like’, which indicated a promising future to conventionally produce xylitol substitute dadih. Therefore, the outcome of this study has shown that xylitol is potentially to be utilize as sugar substitute for dadih production.